2019
DOI: 10.3847/1538-4357/ab3a4d
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic Observations of an Erupting Mini-filament-driven Two-sided-loop Jet and the Applications for Diagnosing a Filament Magnetic Field

Abstract: The ubiquitous solar jets or jet-like activities are generally regarded as an important source of energy and mass input to the upper solar atmosphere and the solar wind. However, questions about their triggering and driving mechanisms are not completely understood. By taking advantage of high temporal and high spatial resolution stereoscopic observations taken by the Solar Dynamic Observatory (SDO) and the Solar Terrestrial Relations Observatory (STEREO), we report an intriguing two-sided-loop jet occurred on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 114 publications
2
59
0
Order By: Relevance
“…So far, the finding of blowout jets has been confirmed by many observational studies, and now we recognize that the vast majority of solar jets are caused by magnetic flux cancellation rather than flux emergence [63,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. Recently, high-resolution observational studies have shown that two-sided-loop jets are also associated with flux cancellations and include the eruption of mini-filaments inside the base arches [44,46,49,85,86], and two-sidedloop jets occurring in filament channels may be important for causing the eruption of large filaments [87].…”
Section: Observational Feature (A) Morphology and Classificationmentioning
confidence: 99%
See 4 more Smart Citations
“…So far, the finding of blowout jets has been confirmed by many observational studies, and now we recognize that the vast majority of solar jets are caused by magnetic flux cancellation rather than flux emergence [63,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. Recently, high-resolution observational studies have shown that two-sided-loop jets are also associated with flux cancellations and include the eruption of mini-filaments inside the base arches [44,46,49,85,86], and two-sidedloop jets occurring in filament channels may be important for causing the eruption of large filaments [87].…”
Section: Observational Feature (A) Morphology and Classificationmentioning
confidence: 99%
“…An anemone jet exhibits an inverted-Y shape consisting of a straight plasma beam and a bright dome-like base. By contrast, a two-sided-loop jet appears as a pair of plasma beams ejecting in opposite directions from the eruption source region [44][45][46][47][48][49]. Recently, high-resolution observations combined with extrapolated three-dimensional (3D) coronal magnetic fields revealed the fan-spine topology magnetic system of straight anemone jets [50], which consists of a coronal nullpoint, a dome-like fan that represents the [51][52][53][54][55][56][57][58][59][60].…”
Section: Observational Feature (A) Morphology and Classificationmentioning
confidence: 99%
See 3 more Smart Citations